EVALUATION OF ANTI-INFLAMMATORY ACTIVITY OF DIFFERENT EXTRACTS AND ISOLATED LIGNANS OF PHYLLANTHUS AMARUS SCHUM. & THONN. AERIAL PARTS. - P.MADHU KIRAN; B.GANGA RAO (International Journal of Pharma and Bio Sciences, 2013)
Phyllanthus amarus Schum. & Thonn. is an important plant of Indian Ayurvedic system of medicine and its various parts were used traditionally for the treatment of problems related to stomach, wounds, liver and spleen. The objective of this study was to evaluate the anti-inflammatory activity of hexane (PAHE), ethyl acetate (PAEA), methanolic (PAME) extracts and isolated lignans (phyllanthin (PAPH) & hypophyllanthin (PAHP)) of P.amarus aerial parts by using carrageenan induced hind-paw-oedema model. The tested extracts (125, 250 & 500mg/kg b.w) and lignans (1.3x10-5 & 2.6x10-5 moles/kg b.w) produced dose dependent significant reduction (p<0.05–0.001) in carrageenan-induced rat paw oedema. The standard drug, Indomethacin at dose 1.3×10-5 moles/kg b.w reduced oedema by 62.01±0.22% and the total (AUC) paw oedema by 69.09±0.15% respectively. The results suggested that the tested extracts and lignans possess in vivo anti-inflammatory activity and the exhibited activity was comparable with the standard drug Indomethacin.